A ascendência da Doença de Chagas aguda como uma doença veiculada por alimentos - CUNHA, Laisy Nazaré Araújo da (2023)
Introduction: Foodborne diseases are spread through physical, chemical or biological agents. Chagas disease (CD) represents an infectious condition whose etiological agent is the flagellate hemoprotozoan Trypanosoma cruzi, which has a biphasic clinical course, consisting of an acute and a chronic phase, is classified as a neglected disease and generally oral transmission is related to the consumption of sugarcane juice, açaí, babassu palm, jaci, bacaba and buriti. In acute Chagas disease (ACD), only 10% of the affected population has symptoms, which corroborates the underreporting of cases of affected individuals. Contamination by CD is estimated to be between 6 and 7 million infected individuals worldwide, being predominant in endemic areas of the disease, located in 21 countries in Latin America, including Brazil. In recent years, Brazil has had thousands of confirmed cases of ACD, and the North region was the one most affected by it, as it has been an endemic area for ACD since the 1990s. Objective: To describe the panorama of DCA in the North region of Brazil during the period from 2007 to 2018. Methodology: Cross-sectional, descriptive, and analytical study, using secondary data from public consultation on cases of DCA made publicly available in the Information and Health System of Notification from Brazil. The data used cover only the ACD cases, specifically referring to the Northern region of Brazil during the period from 2007 to 2018. Considering the variables: total number of notified cases, form of disease transmission, infection status, gender, race, range age, area of residence and monthly seasonality of the ACD. A quantitative data approach was performed, with descriptive statistical analysis, with calculations of mean, standard deviation, and percentages. Friedman's test was applied to determine the statistical significance levels between the variables. Results: In the period from 2007 to 2018 in the North region, 2,248 confirmed cases of ACD were registered. Pará was the state with the highest number of notifications, being represented by 85.5% of cases. According to the incidence rate of the states in North region, the state of Pará had the highest one. Regarding gender, 1,212 cases affected males (54%) and 1,036 cases affected females (46%). The most affected races/colors were brown, with 1760 of the cases. The age group that presented the most cases of ACD were people among 20 and 39 years old, totalizing, in all states, 765 occurrences. The main means of transmission detected in North region were orally (1,861). The main place of contamination was associated with the home environment, with 1,551 cases. 1,176 cases occurred in urban areas. The month with the highest number of infections was October, with 353 cases. Conclusion: The ACD in the Northern region of Brazil, from 2007 to 2018, presented a worrisome situation. The pathology mainly affects males, declared to be of mixed race/color, aged among 20 and 39 years old, infected through oral transmission. The notification period occurred predominantly from August to December, a period that matches with the açaí harvest. The need to encourage surveillance and epidemiological and sanitary control actions is highlighted, as well as health education activities, especially regarding to oral transmission.